THE ROLE OF VEGETABLE BREEDING AND MODERN RESEARCHES IN FOOD STABILITY - A. V. Soldatenko; O. N. Pishnaya (Овощи России)
The vegetable production is one of the main factors for food security, as vegetables play an important role in the structure of nutrition. The Federal Scientific Vegetable Center creates competitive varieties and hybrids of vegetable crops that meet market requirements to meet the needs of domestic producers and thereby contributes to food security. As a result of national breeding program, the varieties and hybrids adapted to different growing conditions, with resistance to local races of pathogens, temperature stresses, and ground frosts were developed to provide the sustainable production of vegetables with high nutritional and medicinal qualities. The varieties and hybrids F1 of white head cabbage that have been created for the last 5 years are distinguished from foreign ones by taste qualities, appropriate pickling characteristics with increased sugar, and decreased cellulose contents. The local onion varieties combine long shelf life, early maturing, well bulb formation, high dry matter content (18-20%) and ability to form the bulb for one year. Breeders have developed bee-pollinated and parthenocarpic hybrids of cucumber well adapted to local growing conditions and suitable for open field cultivation in different regions of Russia. Parthenocarpic heterotic hybrids of the multi-propose use, corresponding to the modern variety model with high productivity, early-ripening, bunch ovary disposition, resistance to abiotic stresses, and most harmful diseases. The carrot and red beet varieties with high nutritional qualities, long shelf-life, ecological plasticity that are widely used for seed production have been created. The varieties of Solanaceae crops have been developed to cultivate in Non Chernozem zone, Far East, Western Siberia, the Middle Belt of Russia and the south of Russia, are also suitable for different greenhouse complexes located in different light zones of the Russia. Wide application of varieties produced through national vegetable breeding programs can provide the population with our own products of high quality.